2003
DOI: 10.1021/ja0292849
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Monodispersed Core−Shell Spherical Colloids with Movable Cores

Abstract: Gold nanoparticles have been conformally coated with amorphous silica (using a sol-gel method) and then an organic polymer (via surface-grafted, atom transfer radical polymerization) to form spherical colloids with a core-double-shell structure. The thickness of silica and polymer shells could be conveniently controlled in the range of tens to several hundred nanometers by changing the concentration of the reagent and/or the reaction time. Selective removal of the silica layer (through etching in aqueous HF) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
429
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 564 publications
(441 citation statements)
references
References 19 publications
10
429
0
2
Order By: Relevance
“…(benzyl methacrylate) yolk-shell nanoparticles [15]. This diffusion may result from the presence of defects or less polymerized sites in the amorphous silica.…”
Section: Synthesis Of Au@sio 2 Yolk-shell Nanostructure With Variablementioning
confidence: 99%
See 1 more Smart Citation
“…(benzyl methacrylate) yolk-shell nanoparticles [15]. This diffusion may result from the presence of defects or less polymerized sites in the amorphous silica.…”
Section: Synthesis Of Au@sio 2 Yolk-shell Nanostructure With Variablementioning
confidence: 99%
“…Numerous methods for the synthesis of yolk-shell nanoparticles (or nanorattles) have been developed [15][16][17]; however, studies of their practical application in heterogeneous catalysis have rarely been reported. Yin et al studied the formation of metal oxide hollow nanoparticles using the Kirkendall effect, and employed it to synthesize Pt@CoO yolk-shell nanoparticles [13].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] It has been very successfully applied to the preparation of many nanocomposites, hybrids, and bioconjugates. [11][12][13][14][15][16][17][18][19][20][21][22][23] The advantages of ATRP, in comparison with other CRP processes, include the large range of available monomers and (macro)initiators, the simplicity of reaction setup, and the ability to conduct the process over a large range of temperatures, solvents, and dispersed media. [6,7,24] ATRP (Scheme 1) is a repetitive atom-transfer process between a macromolecular alkyl halide P n ÀX and a redoxactive transition-metal complex Cu I ÀX/ligand in which P n C radicals propagate (rate constant of propagation k p ) and are reversibly formed (rate constants k a and k da ).…”
mentioning
confidence: 99%
“…285,468 With the advent of nanotechnology, there has also been a continuous increase in organic and inorganic core-shell nanoparticle discoveries with exceptional properties. 8 This gave rise to the discovery of several types of core-shell microstructures, such as spherical 256,284,285,468 , hexagonal 469,470 , multiple cores within a single shell 471,472 , onion-like 473,474 , movable core within shell 475,476 , and 2-D structures such as rods [477][478][479] , among others. A general notation is described here in an attempt to standardize the nomenclature used to define core-shell microstructures.…”
Section: Appendix I: Nomenclature For Core-shell Microstructuresmentioning
confidence: 99%
“…An intentional engineered "void" or "hollow", such as in Refs. 475,476 is considered an extra constituent that can be either core and/or shell.…”
Section: Appendix I: Nomenclature For Core-shell Microstructuresmentioning
confidence: 99%